Late Holocene climate: Natural or anthropogenic?. (15th February 2016) - Ruddiman, W. F.; Fuller, D. Q.; Kutzbach, J. E.; Tzedakis, P. C.; Kaplan, J. O.; Ellis, E. C.; Vavrus, S. J.; Roberts, C. N.; Fyfe, R.; He, F.; Lemmen, C.; Woodbridge, J.
Abstract: For more than a decade, scientists have argued about the warmth of the current interglaciation. Was the warmth of the preindustrial late Holocene natural in origin, the result of orbital changes that had not yet driven the system into a new glacial state? Or was it in considerable degree the result of humans intervening in the climate system through greenhouse gas emissions from early agriculture? Here we summarize new evidence that moves this debate forward by testing both hypotheses. By comparing late Holocene responses to those that occurred during previous interglaciations (in section 2), we assess whether the late Holocene responses look different (and thus anthropogenic) or similar (and thus natural). This comparison reveals anomalous (anthropogenic) signals. In section 3, we review paleoecological and archaeological syntheses that provide ground truth evidence on early anthropogenic releases of greenhouse gases. The available data document large early anthropogenic emissions consistent with the anthropogenic ice core anomalies, but more information is needed to constrain their size. A final section compares natural and anthropogenic interpretations of the δ 13 C trend in ice core CO2 . Key Points: Holocene ice core and ocean sediment trends are anomalous compared to previous interglaciations Paleoecology and archaeology show that early farmers emitted large amounts of CO2 and CH4 Large early agricultural emissions are consistent with geochemical constraints